The expression (not equation) is 6 + 7
20
the sum of -2 and 6 and 7 is (-2+6+7)
in the equation 3+4=7, 3 and 4 are the addends. 7 is the sum.
-6 + 7 - 4 = -3
The expression (not equation) is 6 + 7
that's stupid
6+7=x
The sum of six and seven is expressed as six plus seven. The full equation would be six plus seven equals thirteen.
this is actually an equation let the 'sum' be x we are assuming r means are meaning = so x/6 = 7 x=42 so thats the answer
20
the sum of -2 and 6 and 7 is (-2+6+7)
The solution (not sum) to the equation 21 = 3c + 6 is as follows:21 = 3c + 621 - 6 = 3c + 6 - 615 = 3c3c = 153c/3 = 21/3c = 7
x+ y = 8 is one equation; x - y = 6 is another equation add equations and 2x = 14 x = 7 y = 1
-4 + 7 = 3
It is 6+7 = 13.
6 + 7 = 13(Sum means add)